VD_FINDINFO HC / 2015 / 86 vom 28. Januar 2015 - VD Tribunal cantonal (2015)
TRANSACTION JUDICIAIRE, DÉFENSE D'OFFICE, DÉCISION SUR FRAIS | 105 al. 1 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)